(untitled) (Journal of the College of Education for Women, 2019)
The concept of sustainability is one of the modern concepts that influenced the quality of the urban plans for the cities, through the interest in the environmental and social aspects as well as the economic aspect and the need to balance to achieve sustainable development. The research aims to identify the most prominent methods of sustainable urban land use planning and the strategies developed within these approaches to achieve sustainable development. The research started from the problem of a knowledge gap in adopting sustainable approaches and strategies when planning urban land uses for the holy city of Karbala. In the theoretical aspect, the concepts of sustainable development, sustainable planning methodologies and strategies were identified. Several strategies were developed to be applied in the practical aspect by conducting a questionnaire for professionals working in the study area to demonstrate the application of the selected strategies in planning, designing and implementing urban land uses for the holy city of Karbala (Study area). One of the main conclusions of the research is that there is a great weakness in the adoption of sustainable strategies in the planning, design and implementation of urban land uses of the holy city of Karbala. The study recommended the need to adopt sustainable approaches and strategies when planning the urban land uses of the city to achieve sustainable development.